On the Division into Public and Private Law - Raźniak, Maciej (Acta Universitatis Lodziensis. Folia Iuridica, 2024)
The discussion on the division into public and private law (ius publicum) and private law (ius privatum) can be summarized by considering two fundamental issues: (α) the justification of the division and (β) the choice of a criterion for dividing law into public and private. When reading the texts of Polish legal philosophers, it is hard to resist the impression that they do not notice the line separating (α) and (β) and, consequently, the scale of differences between these issues. This is an unacceptable state of affairs. Therefore, the main purpose of this article is to distinguish these two problems more clearly. In particular, we want to show that investigations aimed at determining whether the division between ius publicum and ius privatum is justified may abstract from which theory of division deserves to be distinguished. In practice, both problems, which can be justified both theoretically (supported only by definitions and logical means) and empirically (based on examples from legal dogmatics), are autonomous from each other.